Clinical Pattern of Thoracic Spine Pain (TSP) - Alam, Md Mahfuzul; Hossain, Md Shahadat; Hojaifa, Musa Muhammad; Rahman, Hasan Habibur; Hosain, Mohammad; Rana, Md Sohel; Kamruzzaman, Mohammed; Alam, Md Aminul (Bangladesh Medical Journal, 2022)
Thoracic spine pain (TSP) is defined as pain perceived anywhere in the region bounded superiorly by a transverse line through the tip of the spinous process of T1, inferiorly by a transverse line through the tip of the spinous process of T12, and laterally by vertical lines tangential to the most lateral margins of the erector spine muscles. One year prevalence of TSP ranged from 8.3-38.1% in different Asian countries. A longitudinal observational study was conducted to observe the clinical feature, demographic profile and clinical course of patients, with TSP attending at the Department of Physical Medicine and Rehabilitation (PMR) of Shaheed Suhrawardy Medical College Hospital (ShSMCH). Among the 100 study patients mean age ±SD was 34.76±13.26. Highest number of the patients (45%) belong to 16-30 years age group and male-female vatioo was 3:1. Highest frequency in the level of education 28% belonged to higher secondary or diploma. Twenty six percent (26%) patients were housewife, manual labor 20%, students 19%, sedentary worker 15%, manufacturing and industrial worker 8%, health professional 4%, driver 3% and 5% were in others group. Most of them (71%) belong to <12000 taka monthly income group and 91% patients’ lived in urban area. Duration of thoracic spine pain was found acute (6 weeks) 46%, sub-acute (>6-12 weeks) 16% and chronic (>12 weeks) 38%. Upper TSP was found among 51% of the patients. Onset of pain among the patients 66% was gradual. Mild intensity of pain was reported in 54% patients, moderate 44% and severe in only 2% patients and 64% patients had no radiation. Aggravating factors were found in patients with prolong sitting in 42%. More than one third (36%) patients relieving factor were lying, 24% rest, activity 16% and no relieving factors in 24% patients. Morning stiffness and depression was found 20% and 25% patients respectively. Associated conditions were found as diabetes mellitus (DM) 25%, sleep disturbance 16%, dyspepsia 10%, hypertension (HTN) were in 7% patients and 42% patients had no associated condition. Large number of the patients’ was occupational 46%; rest of the factors were MFPS 16%, degenerative 14% (dorsal spondylosis 5%, cervical spondylosis 6% and lumbar spondylosis 3%, Ankylosing Spondylitis (AS) 7% and traumatic were 6%. Pott‘s disease 4% and 7% patients’ cause were others. According to Numeric Rating Scale in the first visit mild causes were in 54% patients, 44% moderate and 2% severe. In the last visit 69% patients were found mild and rest had no pain (p value=0.001). Assessment of joint tenderness in first visit; 56% patients were in grade 1, 20% grade 2 and 3% in grade 3, 21% patients had no tenderness. In the last visit it was found that only 21% patients in grade 1 and rest 79% had no tenderness (p value=0.001). According to Pain Disability Index in the first visit mild disability was found in 67% patients, moderate 31% and 2% had no disability. In the last visit mild were 74% and 26% had no disability (p value=0.001). Teenager, young adults and adults were the most commonly affected patients with TSP with M:F=1.5:1. Most of the patient of upper TSP presented before 6 weeks; common presenting features were gradual onset, pain was constant in nature, mild to moderate in intensity without radiation, aggravated by prolong sitting and leaning forward, relieved by lying and rest, with no depression and significant morning stiffness. Most of the factors were occupational and MFPS. Occupations were commonly housewife and manual labor. They were improved significantly (p value=0.001) with conventional treatment. Bangladesh Med J. 2021 Sept; 50(3): 26-35